2021
DOI: 10.34172/ijhpm.2021.91
|View full text |Cite
|
Sign up to set email alerts
|

Crowding-Out Effect of Out-of-Pocket Health Expenditures on Consumption Among Households in Mongolia

Abstract: Background: High out-of-pocket (OOP) health expenditures are a common problem in developing countries. Studies rarely investigate the crowding-out effect of OOP health expenditures on other areas of household consumption. OOP health costs are a colossal burden on families and can lead to adjustments in other areas of consumption to cope with these costs. Methods: This cross-sectional study used self-reported household consumption data from the nationally representative Household Socioeconomic Survey (HSES), co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Healthcare is the main aspect of public services, which is related to the livelihood of the country; thus, the government has a responsibility to provide basic healthcare services. Accordingly, the budget structure is adjusted to increase healthcare resources, forming a crowding-out effect [ 47 ]. This can also be analyzed from the perspective of supply and demand, whereby an increased elderly health burden leads to a rise in a society’s healthcare on the demand side; hence, the government has to increase the fiscal investment to meet the growing health demand on the supply side [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare is the main aspect of public services, which is related to the livelihood of the country; thus, the government has a responsibility to provide basic healthcare services. Accordingly, the budget structure is adjusted to increase healthcare resources, forming a crowding-out effect [ 47 ]. This can also be analyzed from the perspective of supply and demand, whereby an increased elderly health burden leads to a rise in a society’s healthcare on the demand side; hence, the government has to increase the fiscal investment to meet the growing health demand on the supply side [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In other words, it does not consider nor provide insight about households as potential financiers of COVID-19 care. Yet, studies have demonstrated the potential crowding out effects of household health payments on consumptions and on the risk for catastrophic health expenditures [8][9][10]. In Malawi, households contributions towards total health expenditure accounts for 12% and this contribution has been increasing consistently since 2012/13 [11].…”
Section: Introductionmentioning
confidence: 99%
“… 19 , 20 One probable reason is that poor health makes it difficult to accumulate human capital and create an effective labor force, 21 while another is that the burden of disease may increase families and countries’ health-related expenditure. 22 , 23 In fact, the burden of disease among the elderly population could increase families’ caregiving burden, affecting resource allocation and labor employment within the household. 24 , 25 The family caregiving burden depends primarily on the health status of older adults, for example, their ability to perform the activities of daily living and instrumental activities of daily living, and their need for assistance with activity limitations, as well as time spent in a hospital or in bed with a serious illness.…”
Section: Introductionmentioning
confidence: 99%